Are Indonesian High School Students Curious and Creative Enough? An Analysis of Science Curiosity and Creative Thinking Skills in the Merdeka Curriculum Context - Diki Koerniadi; Kusnadi Kusnadi; Rini Solihat (Journal of Education and Teaching (JET), 2026)
This study aimed to assess the levels of science curiosity and creative thinking skills (CreTS) among Grade XI students in state high schools (SMAN) across Sumedang Regency under the Merdeka curriculum. Using a quantitative survey design, data were collected from 210 students across three schools. Instruments included a 20-item Science Curiosity questionnaire (α = 0.82) and a task CreTS essay rubric (inter-rater ICC = 0.78). The study concludes by recommending improved instrument validation, extended response time for CreTS tasks, and deeper post-hoc analysis to better understand inter-school differences.